Serenity Now bombs a World of Warcraft funeral: Negotiating the Morality, Reality and Taste of Online Gaming Practices - Gibbs, Martin Ross; Carter, Marcus; Arnold, Michael; Nansen, Bjorn (AoIR Selected Papers of Internet Research, 2013)
In this paper we examine the controversy surrounding the Serenity Now bombs a World of Warcraft funeral video. This video depicts a group of players in World of Warcraft attacking a group of enemy players as they gather for the in-game funeral of a woman who had recently passed away. We argue that this historical controversy and the ongoing debate surrounding it is a form of “boundary-work” though which players are negotiating the distinction between legitimate and illegitimate online gaming practices. This boundary work involves three strands of demarcations. It has ethical, ontological and aesthetical filaments. The fact that the disputes played out through these entangled filaments haven’t been resolved seven years after the incident indicates that the spaces and boundaries of online interaction remain uncertain and contested. Thus, this paper speaks directly to the themes of appropriation, resistance, and how people negotiate acceptable and unacceptable uses of the internet.